Identification of a 44 kDa protein localized within the endoplasmic reticulum of Trypanosoma brucei brucei - Nandam, D.; Wells, C.W.; Ndegwa, D.; Pearson, T.W. (Cambridge University Press, 1995)
Immunoaffinity chromatography and gel electophoresis were used to isolate a 44 kDa protein that was bound to a 72 kDa chaperone in Trypanosoma brucei brucei. A polyclonal antiserum to the 44 kDa protein was raised in rats and employed in conjunction with chromatography using DEAE-cellulose, Sephacryl S-300, and hydroxyapatite to purify the protein from membranes of bloodstream forms of the trypanosomes. Immunoblot analysis using this antiserum revealed a protein doublet of 44/45 kDa in T. b brucei and a single protein band of 53 kDa in almost equivalent amounts throughout the life-cycle stages of T. congolense. Indirect immunofluorescence using affinity-purified antibodies specific for the 44 kDa protein showed labelling of the perinuclear area and reticular system extending throughout the parasites, suggesting that this protein was located in the endoplasmic reticulum. Localization of the 44 kDa molecule in the endoplasmic reticulum was confirmed by immunoelectron microscopy. Protease protection experiments demonstrated that the epitopes bound by antibody were buried within the membrane or towards the lumenal face of the endoplasmic reticulum. Ruthenium Red overlay of nitrocellulose blots containing the 44/45 kDa doublet suggested that the molecules have the potential to bind calcium. The N-terminal amino acid sequence of the 44 kDa protein showed no sequence similarity to any proteins in the database.